Embodying Relation : Art Photography in Mali - Moore, Allison (Art historian) (Book collections on Project MUSE., 2020)
"In EMBODYING RELATION Allison Moore reads the development of art photography in the 1990s in Mali through the work of Caribbean philosopher Edouard Glissant. Moore engages with Glissant's concept of relation in order to emphasize the ways in which Malian art photography is concerned primarily with making affective connections with viewers, rather than with contesting colonial histories, as has been the case elsewhere. Moore documents an art movement based in Bamako that has used photography as an expressive project, inviting expansive interpretations from viewers (rather than a documentary medium, as was more common during the era of studio photography). The robust photographic archive that accompanies her analysis demonstrates this transition from studio portraits to a portraiture aesthetic that engages the viewer in the simultaneous immediacy and opacity that Moore uses to introduce the reader to a Malian aesthetic. While Bamako has long been recognized as the center of African art photography, the city's capacity to support the growth of the movement is due in large part to the coordination of French patronage, most clearly exemplified by the funding of the Bamako Biennale since 1994. Through combined analysis of the developing aesthetics and institutionalization of the movement, Moore details how Malian photographers established both the market and the taste for photography with a vintage aesthetic in the 1990s. By using Glissant's concept of relation to understand the connections between Bamakois photographers and their global patrons, Moore is able to account for both the photographers' unique aesthetics as well as for the postcolonial acts of mediation they perform. The book's six chapters trace provide a detailed history of Bamakois aesthetics and institutions. Moore first analyzes the political context of the development of the art photography movement following French colonization of Mali and on the heels of its democratization in the 1990s (chapter 1). Subsequent chapters emphasize the importance of French influence and funding on the Bamako Biennale (chapter 3) as well as on Malian "national" institutions such as the National Museum (chapter 5). In so doing, she emphasizes the inherent global and postcolonial nature of the Bamakois art world, and how the photographers whose work she analyzes must navigate these varying institutional and social locations. Moore also considers the rise in prominence of five female photographers, whose careers were facilitated by the Biennale (chapter 6). Chapter 4 turns to Glissant's concept of the archipelago to rethink what Bourdieu might have called the social field of the Bamakois art world as instead an archipelago of institutions borne of different influences and funding structures, yet all interacting within the Biennale-a creolization of Malian and European institutions. This book will be of interest to readers in African studies, art history, art criticism and theory, cultural studies, and museum studies, as well as readers in postcolonial theory and globalization"--